2019
DOI: 10.1111/eth.12980
|View full text |Cite
|
Sign up to set email alerts
|

Individual and social factors affecting the ability of American crows to solve and master a string pulling task

Abstract: Crows and other birds in the family Corvidae regularly share information to learn the identity and whereabouts of dangerous predators, but can they use social learning to solve a novel task for a food reward? Here, we examined the factors affecting the ability of 27 wild‐caught American crows to solve a common string pulling task in a laboratory setting. We split crows into two groups; one group was given the task after repeatedly observing a conspecific model the solution and the other solved in the absence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 68 publications
(90 reference statements)
0
6
0
Order By: Relevance
“…Despite the potential benefits of social learning, public information use appears to be species-specific (Webster et al 2019), and individual biases can have a greater effect on learning than social information even when it is employed (Szabo et al 2017). Even in species known to use social information, social learning may be dependent upon an individual having some experience with novel foraging opportunities, as recently shown in American crows (Corvus brachyrhynchos) (Pendergraft et al 2020) and stickleback species (Webster and Laland 2018). While it is likely that archerfish do use social information, given previous findings suggesting social learning in this species (Schuster et al 2006), many factors may impact the use of social leaning or our ability to detect it.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the potential benefits of social learning, public information use appears to be species-specific (Webster et al 2019), and individual biases can have a greater effect on learning than social information even when it is employed (Szabo et al 2017). Even in species known to use social information, social learning may be dependent upon an individual having some experience with novel foraging opportunities, as recently shown in American crows (Corvus brachyrhynchos) (Pendergraft et al 2020) and stickleback species (Webster and Laland 2018). While it is likely that archerfish do use social information, given previous findings suggesting social learning in this species (Schuster et al 2006), many factors may impact the use of social leaning or our ability to detect it.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these observations, differences in captive housing style do not always result in demonstrable changes in behavior, as compared to wild conspecifics (Gazes, Brown, Basile, & Hampton, ). Further, among corvids and parrots, captive housing has not impeded the ability to test complex social and cognitive research questions, such as those in this special issue ( Clary, Stow, Vernouillet, & Kelly, ; Dufour, Broihanne, & Wascher, ; Heaney, Bastos, Gray, & Taylor, ; Laumer, Massen, Wakonig, Lorck‐Tympner, Carminito, & Auersperg, ; Pendergraft, Lehnert, & Marzluff, ; Morales Picard et al, ; Schwing, Reuillon, Conrad, Noë, & Huber, ; Tassin de Montaigu, Durdevic, Brucks, Krasheninnikova, & von Bayern, ; Wascher, Feider, Bugnyar, & Dufour, ). Additionally, we have used these wild caught, individually housed adult pinyon jays to study various social behaviors, including dominance interactions involving competition over food (Bond, Kamil, & Balda, ; Paz‐y‐Miño C, Bond, Kamil, & Balda, ), food sharing between jays that had never been paired (Duque & Stevens, ), and mesotocin effects on prosocial decision making (Duque et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Note that crows are social animals that are capable of social learning, thus teaching the crows to solve the task in isolation may not have been the most conducive way to train crows. However, previous research has shown that crows do not easily learn to solve tasks using social learning, although they will use it to refine their technique 60 .…”
Section: Methodsmentioning
confidence: 99%